Aquinas's Philosophy of Religion - O'Grady, P. author. aut Link
XIII, 246 p.
Keywords: This is an exploration and analysis of Aquinas's contribution to the philosophy of religion. It examines Aquinas's contexts, his views on philosophy and theology, as well as faith and reason. His arguments for God's existence, responses to objections against God's existence and his characterization of the nature of God are examined.